Crenças de professores de espanhol sobre interação e oralidade na EaD - Gonçalves, Angélica Ilha (2013)
The growth of undergraduate distance courses is the evidence of a new scenario in Brazilian education. This is a reflection of the global trend in enabling different ways for people to continue their studies. However, many questions arise about the process of teaching / learning, such as profile of students, the qualification of teachers for Distance Education (DE), available resources in the environment, interaction, among others. When it comes to an undergraduate degree in a foreign language, these concerns also involve questions related to oral production, as it is one of the skills to be developed in the virtual environment. Thinking of these problems and that the teaching / learning of a foreign language occurs through the interaction between agents, this study aimed to investigate the beliefs of trainer teachers and tutor teachers about the interaction for the development of oral production in two courses of Spanish / DE, of two Brazilian public universities in the southern region of Brazil. Thus, the methodology used in this work is based on the contextual approach of the studies of beliefs (BARCELOS, 2001), which supposes the use of different instruments in order to triangulate data. Therefore, the study included the participation of five teachers; three from the university A and two from the University B, and the data collection was carried out through questionnaires, semi-structured interviews and observation. From the information obtained, we carried out a qualitative analysis seeking the points of convergence and / or divergence of beliefs about the assignments, oral production and interaction in DE. Thus, it was found that although teachers have different roles in DE, this is not an indication that the beliefs of teachers and tutors will be distinct. Moreover, the experience of teachers with present classroom education and distance education influence their beliefs about interaction and oral production. Finally, the action of teachers in the subjects and their beliefs of learning can lead to a change in their beliefs, as could be seen in university B.